Gypsy and Traveller Girls Silence, Agency and Power - Marcus, Geetha; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book presents the untold stories of Gypsy and Traveller girls living in Scotland. Drawing on accounts of the girls' lives and offering space for their voices to be heard, the author addresses contemporary and traditional stereotypes and racialised misconceptions of Gypsies and Travellers. Marcus explores how the stubborn persistence of these negative views appears to contribute to policies and practices of neglect, inertia or intervention that often aim to 'civilise' and further assimilate these communities into the mainstream settled population. It is against this backdrop that the book exposes the girls' racialised and gendered experiences, which impact on their struggles as young people to realise their potential and future prospects. Their narratives reveal the strengths of a distinct community, and the complexity of their silence and agency within the patriarchal structures that pervade the private spaces of home and the public spaces of education. This study also invitesthe reader to reflect on how the experiences of Gypsy and Traveller girls compares with young women from other social backgrounds, and questions if there is more that binds us than divides us as women in the modern world. Gypsy and Traveller Girls will be of interest to students and scholars across a range of disciplines, including sociology, education, gender studies and social policy. .
1.The Outsiders Within: Stereotypes, Definitions and Boundaries -- 2. Power and Silence: The Social Construction of Gypsies and Travellers -- 3. Gypsies and Travellers in Education: Hidden, Deviant or Excluded -- 4. Gypsies, Travellers and Intersectionality -- 5. 'I am not big, fat or just Gypsy': The Racialised and Gendered Experiences of Gypsy and Traveller Girls in School -- 6. 'Honour Thy Father and Mother': Love, Freedom and Control at Home -- 7. Power in Agency: Ambitions, Aspirations and Success -- 8. Conclusion: The Power of Inequality.
Keywords: Sex; Sociology; Social groups; Race; Schools; Gender Studies; Sociology of Family, Youth and Aging; Race and Ethnicity Studies; School and Schooling